Silver isotope fractionation in ore-forming hydrothermal systems. (1st April 2022) - Wang, Jun-Lin; Wei, Hai-Zhen; Williams-Jones, A.E.; Dong, Ge; Zhu, Yuan-Feng; Jiang, Shao-Yong; Ma, Jing; Hohl, Simon V.; Liu, Xi; Li, Yin-Chuan; Lu, Jian-Jun
Abstract: The behavior of silver in hydrothermal ore-forming systems has been the subject of numerous studies. Equilibrium and Rayleigh-type isotope fractionation of silver during transport- and deposition-related processes in silver-bearing hydrothermal ore-forming systems are investigated experimentally and theoretically in this study. The results of open-system evaporation experiments in a simple Ag + –H2 O system show that the transfer kinetics of silver from liquid to vapor follows a second-order kinetic reaction model with activation energy ( Ea ) values of 131.20 ± 14.63 kJ·mol −1 and 145.38 ± 2.93 kJ·mol −1 in neutral and acidic solutions, respectively. No loss of silver from the solution was observed during surface evaporation, and the rate constant, ka, increased exponentially with temperature above 343 K at ambient pressure. During vapor–liquid separation, the vapor is enriched in 107 Ag, whereas the liquid is enriched in 109 Ag. The silver isotope fractionation follows a Rayleigh-type fractionation model with αvapor-liquid factors of 0.99936–0.99985 at 373 K under neutral and acidic conditions, respectively, whereas the temperature-dependent equilibrium isotope fractionation follows the relationship, 1000lnαvapor-liquid  = −0.0039 × 10 6 /T 2 – 0.0037 based on density functional theory (DFT) calculations. This explains the relatively narrow interval of δ 109 Ag values (from −0.3 to +0.4‰) analyzed in Ag-bearing veins from hydrothermal ore-deposits. Based on the bond-strength of Ag to the nearest atoms in minerals, the 109 Ag enrichment decreases in the order pyrargyrite, argentite, proustite, stephanite, native silver, iodargyrite, chlorargyrite. The equilibrium silver isotope fractionation between fluid and mineral during ore formation can be considerable depending on the temperature, the nature of the silver-bearing mineral deposited, whether or not there is vapor–liquid phase separation, and whether there is a reduction of oxidized silver (Ag(+1)) to the reduced form Ag(0). Consequently, the source signatures of δ 109 Ag are altered significantly by transport- and deposition-related processes during ore formation (e.g., boiling, precipitation and reduction). A new silver isotope-geothermometer is proposed based on the equilibrium silver isotope fractionation between argentite and stephanite. This geothermometer, which employs the relationship 1000lnαargentite-stephanite  = 0.0128 × 10 6 /T 2  + 0.0014, can be used to constrain temperature in silver-bearing hydrothermal systems provided that argentite and stephanite are in equilibrium.